2007
DOI: 10.1088/1367-2630/9/4/091
|View full text |Cite
|
Sign up to set email alerts
|

Spectral structure and decompositions of optical states, and their applications

Abstract: We discuss the spectral structure and decomposition of multi-photon states. Ordinarily 'multiphoton states' and 'Fock states' are regarded as synonymous. However, when the spectral degrees of freedom are included this is not the case, and the class of 'multi-photon' states is much broader than the class of 'Fock' states. We discuss the criteria for a state to be considered a Fock state. We then address the decomposition of general multi-photon states into bases of orthogonal eigenmodes, building on existing mu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
111
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(112 citation statements)
references
References 39 publications
1
111
0
Order By: Relevance
“…While in [13] it was shown that the effects can have an impact on quantum communications in space, the main aim of this work is to take advantage of these effects to measure space-time parameters of interest, such as the Schwarzschild radius (mass of the Earth [25].…”
Section: Light Wave-packets Propagating On Earth's Space-timementioning
confidence: 99%
“…While in [13] it was shown that the effects can have an impact on quantum communications in space, the main aim of this work is to take advantage of these effects to measure space-time parameters of interest, such as the Schwarzschild radius (mass of the Earth [25].…”
Section: Light Wave-packets Propagating On Earth's Space-timementioning
confidence: 99%
“…(15) and (16),which ends the proof of (13). Note that knowing the initial state |ψ of S, single photon state |1 ξ of the environment, and the results of measurements (η j , .…”
Section: Conditional Evolution For the Counting Processmentioning
confidence: 58%
“…One of them is a single photon state [12][13][14]. About the methods of its generation and application in quantum of computing and communication one can read in [15][16][17][18][19][20][21][22].…”
Section: Pacs Numbersmentioning
confidence: 99%
See 2 more Smart Citations